Performance analysis of a novel solar desalination system – Part 1: The unit with sensible energy storage and booster reflector without thermal insulation and cooling system. (February 2020) - Cuce, Erdem; Cuce, Pinar Mert; Saxena, Abhishek; Guclu, Tamer; Besir, Ahmet B.
Abstract: Solar desalination systems have a promising potential to meet the clean water demand at global scale in a cost-effective and eco-friendly manner. Therefore, in this research, a novel solar distillation unit with sensible energy storage medium and passive booster reflector is devised, fabricated and experimentally analysed. Within the scope of first part of this research, solar desalination system is not thermally insulated, and there is not any cooling system considered for the aperture glazing to accelerate the distillation process. The tests are conducted for a one-week period in July for a characteristic continental climate. The total water productivity is observed to be 2197.4 ml, which is notable. However, it is concluded that water productivity performance highly depends on the existence of an effective cooling system for the aperture glazing and thermally resistive structure for the external body.